A fast, reliable and cost-effective method to generate tumor organs for therapy screening in vivo. (11th May 2016) - García-Hevia, Lorena; Fernández, Fidel; Casafont, Iñigo; Villegas, Juan Carlos; Fanarraga, Mónica L
Abstract: Innovative anticancer treatments continuously require tissue bioengineering models to test novel therapies. The increasing number of developments based on nanotechnology for cancer therapy or theragnostics demand simple, reliable, fast and cost-effective cancer in vivo models for preclinical testing. However, despite the many tumor models available, very few reproduce the complex intratumoral cell-to-cell interactions as well as the accompanying systemic whole body effects resulting of the tumor organ metabolic, hormonal or growth factor activities, all having critical implications in the success of cancer therapies. Here we describe a reliable tumor model that can be easily reproduced to generate visible solid malignant melanoma tumor organs within a defined period of 5–10 days recapitulating the tumor stroma that is essential for cancer development. These models can be easily evaluated in vivo or by anatomo-pathological procedures. This method provides a fast, reproducible, reliable and cost-effective way to generate solid tumors for in vivo therapy, drug, nanomaterial or imaging probe evaluation, diagnostic or theragnostic screening and validation.